ANALYSIS OF THE NEEDS TARGET GROUP IN THE FINANCIAL SUPPORT SYSTEM OF THE ARMED FORCES OF UKRAINE AND ESTIMATION OF THE ECONOMIC EFFICIENCY OF THE PROJECT SOLUTIONS - SYZOV, Аlim; ARTIUSHENKO, Оleksandr; DYACHENKO, Serhiy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The paper analyses the current state of the financial support system of the Armed Forces of Ukraine, focusing on the growing challenges and limited budgetary resources. Particular emphasis is placed on the need to introduce multi-criteria optimization methods to improve the efficiency of budget management. The main objective of the paper is to assess the cost-effectiveness of implementing design solutions in the financial support system of military units of the Armed Forces of Ukraine, which allows optimizing costs, minimizing risks and increasing the level of responsibility in budget planning.The paper is based on the results of an expert survey involving more than 60 representatives of budget holders at various levels of management of the financial support system of the Armed Forces of Ukraine. The survey helped to identify key areas that need to be optimized, including monitoring and accounting of the status of budget execution, reporting, efficient allocation of limited resources between areas and evaluation of suppliers' proposals in public and defense procurement.A method for evaluating project solutions in the system of financial support of the Armed Forces of Ukraine has been developed. The methodology for analyzing alternative solutions is based on the TOPSIS method (Technique for Order of Preference by Similarity to Ideal Solution), which allows taking into account numerous evaluation criteria and provides an objective ranking of possible options. The results of the calculations show that the most effective alternative is V1, which includes the implementation of software for process automation of the following blocks: a reference book of regulations, tools for allocating limited budget funds between certain areas, and for assessing the effectiveness of expenditures. When calculating according to the developed methodology, based on expert judgements, the expected savings in the institution's budget were obtained at the level of 12-15%.
Keywords: budget; defense expenditures; budget planning; methods of multicriteria optimization; effectiveness of expenditures; effectiveness assessment; expert survey